If a sin 4 x + b cos 4 x = a + b 1 then
a 3 sin 8 x + b 3 cos 8 x = f ( a , b )
find f ( 1 , 1 )
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Any thoughts on how to prove the generalization that Prakhar Bindal brought up?
This Is Shorter Than Mine . I Derived For Any General Pair (a,b) And got the results as 1/(a+b)^3 .
Log in to reply
Can you share how you derived that result? It's interesting that such a result exists, and I wonder if there are any other explanations for it.
Log in to reply
Mine is a very simple approach .
I Simply Replaced (sin)^2 = 1-(cos)^2 in the original condition given
And After A Bit Manipulation
It Yielded Me A Biquadratic Equation In terms of cosx
And to my suprise it turned out to be a perfect square !
whose roots were
(cosx)^2 = b/a+b
and we can apply the pythagorean identity to get
(sinx)^2 = a/a+b
Substituting these values in the expression asked
and manipulating it yielded me 1/(a+b)^3 .
This Result Is True For Any real pair(a,b).
where a+b cant be zero otherwise the original condition given to us will not be valid
Log in to reply
@Prakhar Bindal – Right.
The reason for that is because if se set sin 2 x = s , cos 2 x = c , we have s + c = 1 like you mentioned. Now, by Titu's Lemma ,
a s 2 + b c 2 ≤ a + b ( s + c ) 2 = a + b 1
Thus, we get that a s = b c as the equality condition for the equation to hold.
@Tanishq Varshney This problem seems to be badly phrased to me. The x is extremely dependent on the a , b (and only holds true for particular cases), whereas your statement seems to suggest that we have a trigonometric identity instead.
a = b = 1
s i n 4 x + c o s 4 x = 1 / 2
( s i n 2 x + c o s 2 x ) 2 − 2 s i n 2 x c o s 2 x = 1 / 2
s i n 2 x c o s 2 x = 1 / 4
f ( 1 , 1 ) = s i n 8 x + c o s 8 x
= ( s i n 4 x + c o s 4 x ) 2 − 2 s i n 4 x c o s 4 x
= 1 / 4 − 2 × ( 1 / 4 ) 2 = 0 . 1 2 5
Problem Loading...
Note Loading...
Set Loading...
When a = 1 and b = 1 , then:
⇒ sin 4 x + cos 4 x ( sin 2 x ) 2 + ( cos 2 x ) 2 ( 2 1 − cos 2 x ) 2 + ( 2 1 + cos 2 x ) 2 1 − 2 cos 2 x + cos 2 2 x + 1 + 2 cos 2 x + cos 2 2 x 2 cos 2 2 x cos 2 x ⇒ x = 2 1 = 2 1 = 2 1 = 2 = 0 = 0 = 4 π
Now, we have:
f ( 1 , 1 ) = sin 8 x + cos 8 x = ( 2 1 ) 8 + ( 2 1 ) 8 = 8 1 = 0 . 1 2 5
In response to the Challenge Master...
⎩ ⎪ ⎨ ⎪ ⎧ a sin 4 x + b cos 4 x = a + b 1 b sin 4 x + a cos 4 x = a + b 1 . . . ( 1 ) . . . ( 2 )
( 1 ) − ( 2 ) : ( a 1 − b 1 ) sin 4 x + ( b 1 − a 1 ) sin 4 x = 0
⇒ ( a 1 − b 1 ) sin 4 x sin x ⇒ x ⇒ ( 2 1 ) 4 ( a 1 + b 1 ) ( a + b ) 2 a 2 + 2 a b + b 2 a 2 − 2 a b + b 2 ( a − b ) 2 a = ( a 1 − b 1 ) cos 4 x = cos x = 4 π = a + b 1 = 4 a b = 4 a b = 0 = 0 = b
⇒ x = 4 π , a = b